Research on fatigue life improvement of axle box bushing on 160 km/h power concentrated EMUs - WANG Fengyu; CHENG Haitao; ZHAO Bin; FENG Wansheng; YANG Jun; ZENG Fansheng (机车电传动)
The current study is aimed to extend the service life of axle box bushing mounted on the bogie of 160 km/h power concentrated EMUs by structural optimization, based on the failure cases of such a train component. Firstly, an analysis was made on the boundary conditions of operating cases and failure reasons of the original structure. Then, according to the analysis results, structural improvements were made in many aspects like a rational pre-compression, close-contact rubber profile, streamline cambered surface of steel parts, and suitable thickness of the rubber layer. By the contrast of finite element analysis (FEA) results between the optimized structure and original one, rubber strain decreased by 9.64% and fatigue damage value decreased by 60% for the former, contributing to an obvious improvement in the service life of bushings. Finally, the effectiveness of the optimized structure to improve fatigue performance was proved in the fatigue test, showing a tripled fatigue performance. Through the preliminary evaluation, the fatigue life of bushings in the optimized structure could be extended from 2-5 years to about 8 years, which could improve the operating reliability of the EMUs and reduce unnecessary maintenance. The optimized product has been applied in on-track operation for about 4 years, turning out satisfactory in all performance indexes. The optimization design presented provides a reference for other bushings with a large radial deformation. Specially, the radial pre-compression should be equivalent to fatigue deformation to avoid tensile load on the bushings; aiming at the bushings with a large radial displacement, the close-contact rubber profile could balance rubber surface strain and effectively relieve folds arising from loading on them, thus improve their fatigue life.